Screening of bioflocculant and cellulase-producing bacteria strains for biofloc culture systems with fiber-rich carbon source - Wu, Jinping; Chen, Yifeng; Xu, Xueni; Ren, Wei; Zhang, Xiang; Cai, Xiaoni; Huang, Aiyou; Zeng, Yanhua; Long, Hao; Xie, Zhenyu (Frontiers in Microbiology, 2022)
The biofloc technology (BFT) system has been widely applied in the shrimp and fish culture industry for its advantages in water-saving, growth improvement, and water quality purification. However, The BFT system usually takes a long time to establish and the extra carbon source input increases the maintenance cost of the system. To develop a low-cost and high-efficient BFT system for Litopenaeus vannamei, three bioflocculant-producing bacteria strains (M13, M15, and M17) have been screened from a cellulolytic strain collection in our previous study. All three strains have been identified as Bacillus spp. and can use sugarcane bagasse (SB) as a carbon source, which is a cheap byproduct of the sucrose industry in the tropic area of China. Compared to sucrose, addition of SB and the three strains could improve the biofloc formation rate, biofloc size distribution, ammonia removal rate, and the growth performance of the shrimps. These results have suggest that the bioflocculant and cellulase-producing bacteria strains could promote the biofloc formation and the growth of shrimps by using SB as an economic substitute carbon source in the BFT shrimp culture system.